Sistem Broadcasting Programa 1 (94.6 FM) dan Programa 2 (101.6 FM) di Radio Republik Indonesia Banten - Yoga Dwi Septiyanto; Bagus Dwi Cahyono (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2025)
This research aims to analyze the broadcasting system of Programa 1 (94.6 FM) and Programa 2 (101.6 FM) at Radio Republik Indonesia (RRI) Banten. Using qualitative research methods, data were collected through field observations, interviews, and literature studies. The study identifies two types of broadcasting, namely audio and visual, which utilize digital technologies such as NET software supported by IP Address and VPN. The broadcasting process involves several stages, starting from audio mixers to signal distribution through radio transmitters and digital platforms like YouTube and the RRI website. The findings show that the audio and visual broadcasting systems have been digitized to meet the needs of listeners in the digital era, as well as how equipment such as microphones, mixers, and transmitters are used in the process.